Acquisition of paclitaxel resistance is associated with a more aggressive and invasive phenotype in prostate cancer. Issue 6 (16th April 2013) - Kim, John J.; Yin, Bo; Christudass, Christhunesa S.; Terada, Naoki; Rajagopalan, Krithika; Fabry, Ben; Lee, Danielle Y.; Shiraishi, Takumi; Getzenberg, Robert H.; Veltri, Robert W.; An, Steven S.; Mooney, Steven M.
Abstract Drug resistance is a major limitation to the successful treatment of advanced prostate cancer (PCa). Patients who have metastatic, castration‐resistant PCa (mCRPC) are treated with chemotherapeutics. However, these standard therapy modalities culminate in the development of resistance. We established paclitaxel resistance in a classic, androgen‐insensitive mCRPC cell line (DU145) and, using a suite of molecular and biophysical methods, characterized the structural and functional changes in vitro and in vivo that are associated with the development of drug resistance. After acquiring paclitaxel‐resistance, cells exhibited an abnormal nuclear morphology with extensive chromosomal content, an increase in stiffness, and faster cytoskeletal remodeling dynamics. Compared with the parental DU145, paclitaxel‐resistant (DU145‐TxR) cells became highly invasive and motile in vitro, exercised greater cell traction forces, and formed larger and rapidly growing tumors in mouse xenografts. Furthermore, DU145‐TxR cells showed a discrete loss of keratins but a distinct gain of ZEB1, Vimentin and Snail, suggesting an epithelial‐to‐mesenchymal transition. These findings demonstrate, for the first time, that paclitaxel resistance in PCa is associated with a trans‐differentiation of epithelial cell machinery that enables more aggressive and invasive phenotype and portend new strategies for developing novel biomarkers and effective treatment modalities for PCa patients. J. Cell. Biochem. 114: 1286–1293, 2013. © 2012 Wiley Periodicals, Inc.